Design strategies of ZnO heterojunction arrays towards effective photovoltaic applications. Issue 1 (30th January 2022) - Qiao, Fen; Sun, Kaiyue; Chu, Huaqiang; Wang, Junfeng; Xie, Yi; Chen, Liping; Yan, Tingting
Abstract: ZnO nanorods (NRs) heterojunction arrays have been widely used in photovoltaic cells owing to the outstanding photoelectrical chracteristics, high stability and low cost. The NRs arrays structure can integrate multiple functional components, so that it can exhibit more excellent physical and chemical properties that even independent components do not possess. The design of heterojunction nanostructures can effectively solve the problems of light absorption and carrier transport. First, the synthesis methods of ZnO NRs and their heterojunction arrays were systematically introduced, including traditional chemical vapor deposition (CVD), electrodeposition, hydrothermal method, and so on, the different structures and properties of ZnO NRs heterojunctions were analyzed. Then, the selected materials could be further processed and assembled into NRs array heterojunction with integrated functions were discussed. The strategies of maximizing energy conversion performance (structure optimization, heterojunction, surface plasmon resonance, and doping) were emphatically summarized. In addition, the research progress of ZnO NRs and their heterojunctions in photoelectric energy conversion system were summarized, and the application potential of combining nanostructure design with solar cells was summarized. Finally, the challenges and future development prospects of ZnO NRs and their heterojunction arrays in photovoltaic conversion were pointed out. Abstract : ZnO nanorods and their heterojunction arrays have excellent photoelectric properties. By organically integrating multiple functional components, they exhibit better physical and chemical properties, even those which are not possessed by independent components. By maximizing energy conversion performance strategies (structure optimization, heterojunction, surface plasmon resonance, and doping), the problems of light absorption and carrier transport of solar cells can be effectively solved.